Legal Analysis Of The Implementation Of Criminal Sanctions For Abusing Transportation And Trade Of Subsidized Fuel Oil (Study Of Decision Number 173/PID.B/LH/2024/PN RHL) Judge On The Practice Of Pharmacy Availability - Muhammad Faisal; Risdalina Risdalina; Maya Jannah (CV. AFDIFAL MAJU BERKAH, 2025)
The method used in this thesis research is normative legal research, namely research on problems by looking at the sources of applicable regulations related to the title legal analysis of the implementation of criminal sanctions for abusing transportation and trade of subsidized fuel oil (study of decision number 173 / pid.b / lh / 2024 / pn rhl . The judge's decision in case Number 173 / PID.B / LH / 2024 / PN RHL which has sentenced Defendant II Hendra Saputra alias Hendra bin Jasrianto to imprisonment for 1 (one) year 6 (six) months and a fine of Rp. 250,000,000.00 (two hundred and fifty million rupiah) each with the provision that if the fine is not paid it is replaced with imprisonment for 1 (one) month according to the researcher has reflected a sense of justice . The difference in punishment between the perpetrator and the person who participated in the crime is in accordance with Article 28 of Law Number 4 of 2004 concerning Judicial Power, which states: [1]Judges are required to explore, follow and understand the legal values and sense of justice that exist in society. In considering the severity of the crime, judges are required to also pay attention to the good and evil nature of the defendant. Criminal decisions are not only punishment but also the basis for re-socializing the convict so that it is hoped that he will not commit crimes again in the future so that danger to society can be avoided.